Less barium enema, more colonoscopy: A 12-year nationwide population-based study in Taiwan. Issue 4 (April 2019) - Lee, Kang-Lung; Chiu, Nai-Chi; Su, Chien-Wei; Tseng, Hsiuo-Shan; Lee, Rheun-Chuan; Liu, Chien-An; Lin, Hung-Hsin; Chen, Tzeng-Ji; Chiou, Yi-You
Abstract : Background: Colorectal cancer (CRC) is the second most common and third most fatal cancer in Taiwan. To reduce incidence and mortality rates from cancer, including CRC, the Health Promotion Administration in Taiwan initiated the National Program on Cancer Prevention in 2005. For patients who have a positive fecal occult blood test, colonoscopy is recommended, and double-contrast barium enema (BE) is reserved as an alternative for those who cannot receive colonoscopy. In addition, single-contrast BE is sometimes used in pediatrics to evaluate colonic condition. This study evaluated the usage trends of BE and colonoscopy in Taiwan. Methods: Data from the National Health Insurance Research Database from 2001 to 2013 were used in this study. Patients who received BE and colonoscopy were identified using the procedure codes of the National Health Insurance program. Age-standardized, yearly rates of BE and colonoscopy procedures were calculated. Results: According to the data, the total number of colonoscopies increased 3.7-fold from 2001 to 2013. The compound annual growth rates for BE and colonoscopy were −5.36% and 10.47%, respectively, during the same period. The compound annual growth rates for BE and colonoscopy were −3.89% and 11.64% from 2005 to 2009, and −11.36% and 9.82% from 2010 to 2013, respectively. BE was conducted significantly more frequently than colonoscopy in patients who were aged <12 years and in female patients. Conclusion: Professional association guidelines, national cancer prevention programs, patient and physician preferences, and increasing awareness and knowledge of CRC may all contribute to the increasing use of colonoscopy and the dramatic decline in the use of BE in Taiwan.